Evaluation of saliva as a source of accurate whole‐genome and microbiome sequencing data. Issue 5 (16th May 2021) - Herzig, Anthony F.; Velo‐Suárez, Lourdes; Le Folgoc, Gaëlle; Boland, Anne; Blanché, Hélène; Olaso, Robert; Le Roux, Liana; Delmas, Christelle; Goldberg, Marcel; Zins, Marie; Lethimonnier, Franck; Deleuze, Jean‐François; et al.
Abstract: This study sets out to establish the suitability of saliva‐based whole‐genome sequencing (WGS) through a comparison against blood‐based WGS. To fully appraise the observed differences, we developed a novel technique of pseudo‐replication. We also investigated the potential of characterizing individual salivary microbiomes from non‐human DNA fragments found in saliva. We observed that the majority of discordant genotype calls between blood and saliva fell into known regions of the human genome that are typically sequenced with low confidence; and could be identified by quality control measures. Pseudo‐replication demonstrated that the levels of discordance between blood‐ and saliva‐derived WGS data were entirely similar to what one would expect between technical replicates if an individual's blood or saliva had been sequenced twice. Finally, we successfully sequenced salivary microbiomes in parallel to human genomes as demonstrated by a comparison against the Human Microbiome Project.